DISTRIBUTION OF COUPLED SUPPORT FOR BEEF CATTLE IN ROMANIA – AN ANALYSIS IN THE MOUNTAIN AREA - Mariana GRODEA; Iuliana IONEL; Diana-Maria DRIGĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the period 2015-2019, the beef cattle farming sector (beef cows, beef bulls, crossbred cows with beef breeds, young male and female beef cattle and crossbreeds of young male or female young cattle with beef breeds) benefited from a total amount of 52 million euros as VCS, which represented 7.8% of the total value of coupled support for the livestock sector. The increase in the number of beef cattle, from 8 thousand heads in 2015 to 53 thousand heads in 2019, led to the decrease of the VCS value/head from 1312 euros/head in 2015 to 237.4 euros/head in the year 2019. The comparative analysis (2019 versus 2016) of the coupled support distribution by farm size classes reveals a relatively similar situation. Most beef cattle approved for coupled support, both in 2016 and in 2019, are found on the farms from the size class 101-250 heads, 31.1% and 33.5% respectively, representing 7.6% and 5.8% of beneficiaries.